Implementing Community-based Health Planning and Services in impoverished urban communities: health workers' perspective - Adanna Uloaku Nwameme; Philip Teg-Nefaah Tabong; Philip Baba Adongo (BMC, 2018)
Abstract Background Three-quarters of sub-Saharan Africa's urban population currently live under slum conditions making them susceptible to ill health and diseases. Ghana characterizes the situation in many developing countries where the urban poor have become a group much afflicted by complex health problems associated with their living conditions, and the intra-city inequity between them and the more privileged urban dwellers with respect to health care accessibility. Adopting Ghana's rural Community-Based Health Planning and Service (CHPS) programme in urban areas is challenging due to the differences in social networks and health challenges thus making modifications necessary. The Community Health Officers (CHOs) and their supervisors are the frontline providers of health in the community and there is a need to analyze and document the health sector response to urban CHPS. Methods The study was solely qualitative and 19 in-depth interviews were conducted with all the CHOs and key health sector individuals in supervisory/coordinating positions working in urban CHPS zones to elicit relevant issues concerning urban CHPS implementation. Thematic content data analysis was done using the NVivo 7 software. Results Findings from this appraisal suggest that the implementation of this urban concept of the CHPS programme has been well undertaken by the health personnel involved in the process despite the challenges that they face in executing their duties. Several issues came to light including the lack of first aid drugs, as well as the need for the Integrated Management of Neonatal and Childhood Illnesses (IMNCI) programme and more indepth training for CHOs. In addition, the need to provide incentives for the volunteers and Community Health Committee members to sustain their motivation and the CHOs' apprehensions with regards to furthering their education and progression in their careers were key concerns raised. Conclusion The establishment of the CHPS concept in the urban environment albeit challenging has been fraught with several opportunities to introduce innovations which tailor the rural milestones to meet urban needs. Modifications such as adjusting timing of home visits and renting accommodation in the communities for the CHOs have been beneficial to the programme.